Association Between Uric Acid to High‐Density Lipoprotein Cholesterol Ratio and Kidney Function in Patients With Primary Aldosteronism: A Cross‐Sectional Study - Meng‐Bo Wu; Rui Wang; Qing‐Tian Zeng; Wen‐Liang Shuai; Hang‐Cheng Zhang; Yi‐Fei Dong (The Journal of Clinical Hypertension)
ABSTRACT The relationship between the uric acid to high‐density lipoprotein cholesterol ratio (UHR) and kidney function in patients with primary aldosteronism (PA) is unclear. Therefore, this research explored the link between the UHR and kidney function in PAs. This research was conducted at the 2nd Affiliated Hospital of Nanchang University and involved PA individuals hospitalized between October 2017 and April 2022. A total of 653 eligible participants were included in the analysis for this research. The kidney function was assessed by the estimated glomerular filtration rate (eGFR), which is calculated using the modification of diet in renal disease (MDRD) equation. Chronic kidney disease (CKD) was defined as an eGFR <60 mL/min per 1.73 m2 or the ratio of urine microalbumin to creatinine (UACR) ≥30 mg/g. The study used multivariable‐adjusted linear regression analyses to investigate the association between log‐transformed UHR levels and, eGFR and CKD. After multivariable adjustments, the results indicated an inverse association between Lg‐UHR and eGFR (per SD increment; β: −9.02; 95% CI: −11.59, −6.46). Compared to PA patients with the lowest level of Lg‐UHR (T1), patients with the highest level of Lg‐UHR (T3) had a lower eGFR (β: −20.14, 95% CI: −26.25, −14.04). Conversely, Lg‐UHR and CKD showed a positive association cross‐sectionally (per SD increment; OR: 1.67; 95% CI: 1.26, 2.23). Compared to PA patients in T1 level, patients in T3 level had a higher prevalence of CKD (OR: 2.52, 95% CI: 1.26, 5.05). In patients with PA, UHR is inversely associated with eGFR and positively associated with CKD.